Estudio de factibilidad para la creación de un minimarket en el recinto Calope de Garrido del cantón Pangua, provincia de Cotopaxi. - Calero Chicaiza, Gilda Gissela (2024)
This research was carried out to develop a feasibility study for creating a minimarket in the Calope de Garrido precinct, Canton Pangua, Province of Cotopaxi, which was motivated by the growing consumption needs among potential consumers. The methodology determined the use of deductive, analytical, and empirical methods, and the types of research used were bibliographic and field, with a descriptive level, to collect information, interviews, and surveys were applied to store owners and potential consumers, for which purpose questionnaires were designed and submitted to the respective validation processes by experts. The market study determined the unsatisfied demand for the year 2024 in rice 38.548, sugar 30.169, soft drinks 18.713, toothpaste 51.607, and detergents 55,007. In the technical study, a goal expected to capture 5% of the unsatisfied demand reflected an amount of 1,898 pounds per year, for oil was established to capture 5% with an amount of 2220 liters, and sugar was placed at 1,845 pounds per year. In the case of soft drinks, 921 liters is equal to 3%, 1,524 units of toothpaste per year, and 1,625 units of detergents are expected to be collected. The location contemplated the essential aspects and determined the specific location in the Calope de Garrido precinct. The economic study identified values of the initial investment of $12,695.06, which gave a net profit of $42.004,48. The NPV was $83,961.36, IRR: was 52%, C/B: was 1.61. Given the results of the market study, technical, economic, and financial study, which were favorable, in conclusion, the creation of the minimarket is feasible because it represents viability and profitability for the owners who will be the principal beneficiaries of the development of the local entrepreneurship proposal.